2021
DOI: 10.1097/fjc.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of the Direct Oral Anticoagulants Dosing in the Middle East Gulf Region

Abstract: Direct oral anticoagulants (DOACs) have proven efficacy to prevent cardioembolic strokes. Data are scarce about the appropriateness of DOAC dosing in the Middle East. We investigated the prevalence of inappropriate DOAC dosing in the region. A cross-sectional study was conducted at our hospital between April 2015 and February 2019 of patients receiving 1 of the 3 available DOACs. Patients with incomplete data sets, those prescribed DOACs for indications other than atrial fibrillation, on DOACs for <30 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A history of minor bleed (HAS-BLED <3 vs HAS-BLED ≥3) was associated with an increased risk of underdosing 8 9 14 22 27 30–39. Similarly, an increased risk of underdosing was observed with age ≥65 years and age ≥75 years (reference category: ≤65 years) 8 9 14 22 27 30–39.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A history of minor bleed (HAS-BLED <3 vs HAS-BLED ≥3) was associated with an increased risk of underdosing 8 9 14 22 27 30–39. Similarly, an increased risk of underdosing was observed with age ≥65 years and age ≥75 years (reference category: ≤65 years) 8 9 14 22 27 30–39.…”
Section: Resultsmentioning
confidence: 89%
“…Fifteen studies conducted regression analyses on the drivers of inappropriate NOAC dosing, examining patient demographics (age, sex and weight), comorbidities (diabetes (type unspecified), hypertension and congestive heart failure), stroke risk factors (history of prior stroke, CHA 2 DS 2 -VASc score and CHADS 2 score), renal function (CrCl and estimated glomerular filtration rate (eGFR) and bleeding risk (HAS-BLED and history of minor bleed) 8 9 14 22 27 30–39…”
Section: Resultsmentioning
confidence: 99%
“…In particular, NOAC over-dosing was associated with increased all-cause mortality, while NOAC under-dosing was associated with higher rates of hospitalization for cardiovascular conditions ( 27 ). Another study demonstrated that inappropriate NOAC prescriptions were more likely to occur in the older adult population ( 28 ). This is the most worrisome finding because the risk of stroke increases significantly with age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to better safety outcomes with apixaban than warfarin, other factors should be considered before selection of anticoagulation agents, including drug–drug interactions, cost, and applicability of routine INR checks. In addition, apixaban dosing should follow the FDA recommendations, considering that Anouassi et al 21 reported subtherapeutic dosing among prescribers practicing in the Gulf region. In our study, apixaban was dosed according to FDA recommendations for treatment of VTE, which could explain the lower rates of VTE recurrence.…”
Section: Discussionmentioning
confidence: 99%